Novel electrochemical method for monitoring and predicting localized corrosion - Naing Naing Aung (2008)
This PhD research project was conducted to develop new electrochemical methods for studying localized corrosion processes in various environment. An electrochemically integrated multi-electrode array, namely the wire beam electrode (WBE) and electrochemical noise analysis (ENA) was applied in novel combinations to study several typical localized corrosion systems in a creative manner.